Changes in Circulating BDNF in relation to Sex, Diet, and Exercise: A 12-Week Randomized Controlled Study in Overweight and Obese Participants - M. Glud; T. Christiansen; L. H. Larsen; B. Richelsen; J. M. Bruun (Journal of Obesity)
Circulating BDNF is higher in women than in men and suggested to be affected by changes in food intake, body weight, and exercise. The purpose of this study was to compare BDNF concentrations in women and men during a 12-week weight loss intervention. Using a previously published 12-week randomized study, serum BDNF was assessed at baseline and after 12 weeks using an enzyme-linked immunosorbent assay method. Fifty overweight or obese but healthy individuals (26 women, mean age of 36.4 ± 7.9 years; 24 men, mean age of 38.0 ± 5.9 years) were included and allocated into three groups: exercise-only (EXO; 12 weeks of aerobic exercise and isocaloric diet), diet-only (DIO; 8 weeks of very low energy diet (VLED 600 kcal/day) followed by a 4-week weight maintenance diet), or diet and exercise (DEX; 12 weeks of aerobic exercise in parallel with 8 weeks of VLED (800 kcal/day) followed by a 4-week weight maintenance diet). At baseline, BDNF levels were 25% higher in women compared to men (p=0.006). Body weight was reduced in all intervention groups (p<0.006). Exercise (EXO group) induced a 22% reduction in circulating BDNF in men (p=0.037) and women (p=0.080). In the DIO and DEX groups, a significant reduction in BDNF levels (29.9%; p=0.035 and 32.5%; p=0.003, respectively) was observed in women but not in men. In conclusion, circulating BDNF was significantly changed by diet alone or combined with exercise in women and only by exercise alone in men. This suggests that changes in circulating BDNF depend on weight loss methods (diet/exercise) as well as sex.